ANALYSIS OF TOURISM MARKETING STRATEGIES ON TOURIST VISITS TO PAGARALAM CITY - Indri Ariyanti; Fithri Selva Jumeilah; Indriani Indah Astuti; Riana Mayasari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Technological development has changed the social order in society. Several countries are starting to lead to the 5.0 industrial revolution. Technological transformation brings society to digital civilization in almost all aspects of life. This study aimed to analyze the influence of Content Marketing and e-WOM on Revisit Intention. Through a quantitative research approach, the population of this study was people who had visited tourist destinations in Pagar Alam City with a total of 120 respondents. Data were collected by distributing questionnaires to respondents. Based on the results, Content Marketing and e-WOM simultaneously had a significant influence on Revisit Intention. However, partially, the Content Marketing variable had no significant influence on revisit intention. Meanwhile, e-WOM turned out to have a significant influence on Revisit Intention partially. This is because there are other more influential variables than the two variables in this study.